Primary versus Metastatic Gastrointestinal Melanoma: A Rare Case and Review of Current Literature. (29th August 2016) - Simons, Malorie; Ferreira, Jason; Meunier, Rashna; Moss, Steven
Abstract : Gastrointestinal (GI) melanomas are a rare diagnostic entity. Although there have been cases of melanomas solely in the GI tract, many debate their true origin: the gut versus a distant, undetected primary lesion that regressed known as melanoma of unknown primary. We present a case that involved diagnosing a GI melanoma and then backtracking to find a possible primary source. We review the most recent literature regarding possible etiologies of primary GI melanomas and how to differentiate whether it has a primary, metastatic, or unknown origin.